"Living in History*": Bush, World War II, and the Use of Historical Analogies in the Gulf Crisis. Issue 3 (17th August 2022) - Jones, Rachael
Abstract : On August 2, 1990, Iraq invaded Kuwait. Over the next three days, President George H.W. Bush, his advisors, and world leaders would debate and determine the United States' goals and objectives. These decisions would compel the country's trajectory for the next several months. The process regarding the determination to reverse Iraqi aggression, if necessary with force, provides a compelling case study regarding the use of historical analogies in presidential decision making. Using original archival research, this in‐depth history reveals that historical analogies played a key role in shaping policy on the eve of the Iraq War. This article provides the most complete history of the use of analogies in the initial response to the Gulf crisis to date, as well as valuable insight into the Gulf War, President H.W. Bush, and the process of presidential decision making.